2013
DOI: 10.1007/s10608-013-9525-4
|View full text |Cite
|
Sign up to set email alerts
|

Are Negative Automatic Thoughts Associated with ADHD in Adulthood?

Abstract: Recent randomized controlled trials indicate that cognitive-behavioral therapy (CBT) for adults with attention-deficit/hyperactivity disorder (ADHD) is an efficacious treatment. Although treatments for adults with ADHD target negative automatic thoughts, there is a lack of empirical evidence demonstrating that such cognitions are associated with ADHD. The goal of this study was to assess the relationship between ADHD and negative automatic thoughts typically associated with depression in a group of adults diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 33 publications
(37 reference statements)
3
28
0
Order By: Relevance
“…Direct empirical support for this hypothesis in children with ADHD has recently been accumulating (McQuade et al 2011; Ostrander and Herman 2006). In adults, a recent chart review study of 81 patients diagnosed with ADHD found that inattentive symptoms were associated with negative automatic thoughts even after accounting for depression symptom severity, although patients with comorbid ADHD and depression showed even higher levels of negative automatic thoughts than patients with ADHD alone (Mitchell et al 2013). These findings support further consideration of maladaptive cognitive processes in depression in adults with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Direct empirical support for this hypothesis in children with ADHD has recently been accumulating (McQuade et al 2011; Ostrander and Herman 2006). In adults, a recent chart review study of 81 patients diagnosed with ADHD found that inattentive symptoms were associated with negative automatic thoughts even after accounting for depression symptom severity, although patients with comorbid ADHD and depression showed even higher levels of negative automatic thoughts than patients with ADHD alone (Mitchell et al 2013). These findings support further consideration of maladaptive cognitive processes in depression in adults with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting such patterns of negative maladaptive thoughts is important since there is strong evidence that ADHD in adults is associated with increased risk for depression and anxiety disorders and, more specifically, that ADHD in adults is also associated with the patterns of negative and distorted thinking associated with these disorders (Abramovitch & Schweiger, 2009; Knouse, Zvorsky, & Safren, 2013; Mitchell, Benson, Knouse, Kimbrel, & Anastopoulos, 2013; Strohmeier, Rosenfield, DiTomasso, & Ramsay, 2016). However, there is growing recognition that maladaptive patterns of thinking are not restricted to these “negative” thinking styles in adult ADHD (Knouse & Mitchell, 2015).…”
mentioning
confidence: 99%
“…After a lifetime of perceived failure and negative feedback from others, it stands to reason that adults with ADHD are likely to develop patterns of negative, self-defeating thoughts that undermine their behavior change efforts (Safren, Perlman, Sprich, & Otto, 2005). Such cognitions are elevated in adult ADHD samples (Mitchell, Benson, Knouse, Kimbrel, & Anastopoulos, 2013) and may put them at-risk for depression (Knouse, Zvorsky, & Safren, 2013). Yet, clinically, we have observed that our adult patients with ADHD report another flavor of cognition that can be just as problematic in its relationship with skill use, for example:

“I'm a good person, so things are just going to work out for me.”

…”
mentioning
confidence: 99%